Implementasi Teori Aksi dalam Pemberdayaan Masyarakat melalui KUBE (Kelompok Usaha Bersama) sebagai Salah Satu Upaya Peningkatan Konsep Diri Disabilitas - Kurnia Lystiarini; Ike Mardiati Agustin; Asri Laksmi Riani (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Empowerment can be seen as a process and interrelated goals among various elements of society, one of which is a group of people with disabilities, a phenomenon that exists in today's society they tend to pity rather than provide opportunities for people with disabilities to be independent, this causes self-concept problems such as lack of self-confidence, isolated and inferior from society. Objectives: Efforts to improve social welfare for people with disabilities can be done by providing opportunities for disabled groups to play an active role in people's lives through the Joint Business Group (KUBE) through the Diffable Action Theory approach as actors pursuing goals in situations where norms direct in choosing alternative ways and tools to achieve the goal of empowering people with disabilities. Method: This community service was prepared using a descriptive analytical method with survey method, the sample was taken by purposive sampling on 11,006 people with disabilities in Wonogiri Regency, from a total population of 1,033,857 or 1%. Result: There has been an increase in the self-concept of people with disabilities before and has been given reinforcement about KUBE in increasing independence. Conclusion: The results of the survey in this work found that 8 Joint Business Groups (KUBE) in Wonogiri Regency were able to increase the independence and self-concept of disabled groups. The recommendations from this study can be used as a baseline for further research.